Molecular characterization of two tobacco varieties treated with gamma radiation using the ISSR technique - الرياحي, منار; صالح قبيلي ,; مجد درويش,; نزار معلاّ , (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out in the Faculty of Agriculture, Tishreen University, the Tobacco Research Center and the Atomic Energy Commission, using the Virginia and Baladi tobacco varieties. The seeds were treated with several doses of gamma radiation (0-100-200-and 300 Gy) to study the effect of radiation at the molecular level using the ISSR technique. The DNA was extracted by CTAB method and amplified by PCR using ISSR technology with 22 primers, The results of amplification in the Virginia variety gave 672 total bundles, with an average of 30.54, of which 62 were morphologically polymorphic, with a rate of 9.2%. In the Baladi variety ,it gave 622 total bundles, with an average of 28.27 for each primer. The number of morphologically multiple bundles was 62, with a rate of 9.96%. In both cultivars, the primer D8 excelled in the total number of bundles produced. The ISSRS results were used to create an UPGMA chart for both varieties, which showed the distribution of coefficients in two main groups: The first group included the Virginia variety, the treatment V3, and the second group included the treatments V-V1-V2 with a genetic distance of 0.25, where V1 and V2 were the closest genetically with a similarity of 95% and the furthest was V3 with a genetic divergence of 25%. In the Baladi variety, treatment B3 was placed in a separate group, and treatments B- B1-B2 were placed in a second group with a genetic distance of 0.25. B1 and B2 were the closest genetically with a similarity of 91%, and the furthest was B3 with a genetic divergence of 23%.The results indicate the effectiveness of the ISSR technique in determining the effect of irradiation among tobacco varieties. Key words: Nicotiana tabacum – Gamma rays - Molecular characterization – ISSR